Mitigating Income Inequality in Bali Province, Indonesia - Amrullah, Muhammad; Wahyudi, Setyo Tri; Ekawaty, Marlina (Muhammadiyah University Press, 2020)
Studying the distribution of income in a region is an important topic to know about the factors that influence the distribution of income, then find out the factors that are the solution to problems related to income distribution, and later can minimize differences in income distribution disparities between regions. This paper estimates the relationship between Unemployment, Labor Participation, Employed Workers, Elementary School Graduates, Junior High School Graduates, and Senior High School Graduates to Income Inequality in 9 districts/cities in Bali Province throughout 2008-2018. This study estimates the relationship of six independent variables to income inequality as the dependent variable using multiple panel regression analysis with the Fixed Effect Model (FEM) model in 9 districts/cities in Bali Province over period 2008-2018. The results of this study found that Unemployment, Labor Participation, Employed Workers, Elementary School Graduates, Junior High School Graduates, and Senior High School Graduates are significant to Income Inequality. Unemployment and Junior High School Graduates positively affect to Income Inequality, then Labor Participation, Employed Workers, Elementary School Graduates, and Senior High School Graduates negatively affect to Income Inequality.